Cassava root crown phenotyping using three-dimension (3D) multi-view stereo reconstruction - Sunvittayakul, Pongsakorn; Kittipadakul, Piya; Wonnapinij, Passorn; Chanchay, Pornchanan; Wannitikul, Pitchapor; Sathitnaitham, Sukhita; Phanthanong, Phongnapha; Changwitchukarn, Kanokphu; Suttangkakul, Anongpat; Ceballos, Hernan; Vuttipongchaikij, Supachai (Springer, 2022)
Phenotypic analysis of cassava root crowns (CRCs) so far has been limited to visual inspection and very few measurements due to its laborious process in the feld. Here, we developed a platform for acquiring 3D CRC models using close-range photogrammetry for phenotypic analysis. The state of the art is a low cost and easy to set up 3D acquisition requiring only a background sheet, a reference object and a camera, compatible with feld experiments in remote areas. We tested diferent software with CRC samples, and Agisoft and Blender were the most suitable software for generating high-quality 3D models and data analysis, respectively. We optimized the workfow by testing diferent numbers of images for 3D reconstruction and found that a minimum of 25 images per CRC can provide high quality 3D models. Up to ten traits, including 3D crown volumes, 3D crown surface, root density, surface to-volume ratio, root numbers, root angle, crown diameter, cylinder soil volume, CRC compactness and root length can be extracted providing novel parameters for studying cassava storage roots. We applied this platform to partial-inbred cassava populations and demonstrated that our platform provides reliable 3D CRC modelling for phenotypic analysis, analysis of genetic variances and supporting breeding selection.